The levels of bioactive compounds found in raw and cooked Canadian pulses - Stone, A K (Food science and technology international = Ciencia y tecnologia de los alimentos internacional, 2021)
The effect of cooking on the levels of bioactive compounds (oligosaccharides, polyphenols and saponins, and vicine/convicine for faba bean only) were examined in a wide range of Canadian pulses. The total oligosaccharide concentrations were reduced ∼40% for chickpea, 11-81% for lentils, 41-43% for faba beans, 10-51% for beans, and 20-44% for peas. Individual oligosaccharides, raffinose, ciceritol, stachyose and verbascose, increased or decreased in the cooked samples depending on each pulse sample. Cooking reduced the total polyphenol content by 13-25% for chickpeas, 0-83% for lentils, 47-54% for faba beans, 47-54% for beans, and 48-70% for peas. And, the total saponin concentrations were reduced by 11-30% for chickpeas, 0-40% for lentils, 32-46% for beans, 14-30% for peas and increased by 8-26% in faba bean. The vicine and convicine levels in faba bean were reduced by 26-38% with cooking. The reduction in bioactive compounds after cooking depended on the specific compound and specific type of pulse. This large analyses of 20 different pulse samples allows for comparison between and within different types of pulses